The Employer Size-Wage Effect - Brown, Charles; Medoff, James (Journal of Political Economy, 1989)
The authors consider six explanations for the positive relationship between employer size and wages: large employers (1) hire higher-quality workers, (2) offer inferior working conditions, (3) make more use of high wages to forestall unionization, (4) have more ability to pay high wages, (5) face smaller pools of applicants relative to vacancies, and (6) are less able to monitor their workers. They find some support for the first of these, but there remains a significant wage premium for those working for large employers. Copyright 1989 by University of Chicago Press.